Fiqhu al bu'd al iqtishadi li azimati al'alamin al mu'ashirah muqaddimatani manhajitani - Ali Abd Al-Mun'im Al-Mishri (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2008)
The contemporary crisis of global financial, then economic, systems usually analyzed, interpreted, and perceived to be solved based on variables from within these two systems. In such frame of thinking financial assets and leverage, mortgage crisis, stock markets, etc are proposed to interpret the crisis, leaving behind many other vital variables. Vital variables are those of epistemological, axiological and ontological systems that form and guide the financial and economic actors in capitalist-globalized system. Through two methodological introductions, this article, this article proposes the contemporary crisis as an aspect named ‘economic’ of another deeper, more influential, and circumambient; which the article named